Case Report: A minimally disruptive technique for the management of frozen leads - Chang, Su-Huan; Lin, Kuan-You; Yu, Chih-Chieh (Frontiers in Cardiovascular Medicine, 2025)
During pacemaker generator replacement, difficulties may arise with the set screw not being properly engaged, a situation referred as a “frozen lead”. We reported a case of an 88-year-old woman with a 15-year-old generator and increasing impedance of the right atrial lead. The disruption of the silicone plug and removal of the hidden metal ring facilitated successful disconnection of the generator without damaging the lead. Postoperative assessments demonstrated normalized right atrial lead impedance and stable parameters at follow-up. This case highlights the effectiveness of a minimally invasive approach to managing frozen leads, providing valuable insights in similar clinical scenarios.